2016
DOI: 10.1063/1.4958461
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Convergence of many-body wave-function expansions using a plane-wave basis in the thermodynamic limit

Abstract: Basis set incompleteness error and finite size error can manifest concurrently in systems for which the two effects are phenomenologically well-separated in length scale. When this is true, we need not necessarily remove the two sources of error simultaneously. Instead, the errors can be found and remedied in different parts of the basis set. This would be of great benefit to a method such as coupled cluster theory since the combined cost of n 6 occ n 4 virt could be separated into n 6 occ and n 4 virt costs w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 73 publications
(114 reference statements)
3
29
0
Order By: Relevance
“…26,46,47 . CCSD and CCSDT have been applied to the finite three-dimensional (3D) UEG 14,29,34,[48][49][50] . Shepherd 50 has extrapolated finite CCSD/CCD results in the 3D UEG to the thermodynamic limit and has compared them to Ceperley and Alder's DMC energies 37 (see figure 2c in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…26,46,47 . CCSD and CCSDT have been applied to the finite three-dimensional (3D) UEG 14,29,34,[48][49][50] . Shepherd 50 has extrapolated finite CCSD/CCD results in the 3D UEG to the thermodynamic limit and has compared them to Ceperley and Alder's DMC energies 37 (see figure 2c in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] Although coupled-cluster theory has been successfully applied to an increasing number of atomistic semiconductors and insulators, 14,15,[32][33][34][35][36][37] its applicability for metals has been primarily focused around the UEG, also known as jellium. 29,[38][39][40][41][42][43][44][45] Despite their reasonable accuracy, these calculations have demonstrated the typical slow convergence of the correlation energy as a function of the number of virtual (unoccupied) orbitals included. 11,40,46,47 This slow convergence is especially problematic because of the high cost of coupled-cluster calculations with large basis sets.…”
Section: Introductionmentioning
confidence: 99%
“…29,[38][39][40][41][42][43][44][45] Despite their reasonable accuracy, these calculations have demonstrated the typical slow convergence of the correlation energy as a function of the number of virtual (unoccupied) orbitals included. 11,40,46,47 This slow convergence is especially problematic because of the high cost of coupled-cluster calculations with large basis sets. For example, coupled-cluster theory with single and double excitations (CCSD) has a computational cost that scales as O(N 2 M 4 ), where N and M are the number of electrons and basis functions respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, these include the coupled cluster method and its different approximations, such as the widelyused coupled cluster singles and doubles plus perturbative triples theory (CCSD(T)) [7]. Yet despite the great advances of modern coupled cluster theory approximations and their applications to molecules, surfaces, and solids it remains difficult to treat metallic systems at the same level of theory, with the exception of applications to simple model Hamiltonians such as the uniform electron gas [8][9][10][11][12][13][14][15][16][17][18]. This constitutes a significant obstacle in modern computational materials science, where accurate benchmark results obtained with high-level theories for all types of materials are desperately needed to complement computationally more-efficient but less-accurate density functional theory calculations.…”
mentioning
confidence: 99%
“…However, for the uniform electron gas, which is the simplest and most popular metallic model Hamiltonian, each of these barriers can be overcome. [9,[13][14][15][16][17][18] Through scrupulous accounting for error and its cancellation, we have found that it is possible to converge each component of the total energy to reach benchmark accuracy. On the journey to a universal application of single-reference coupled cluster theory to all solids, the final hurdle is to transfer these successes to real metals.…”
mentioning
confidence: 99%